2023
DOI: 10.2486/indhealth.2022-0033
|View full text |Cite
|
Sign up to set email alerts
|

Pros and cons of quick returns—a cross-sectional survey among Swedish nurses and nurse assistants

Abstract: Short rest (<11h) between evening and day shifts -known as quick returns (QRs)impede recovery and may impair health. Nevertheless, QRs remain popular among some shift workers. This study explores nurses' and nursing assistants' perceptions of the merits and demerits of QRs from individual and organizational perspectives. Participants were recruited from eleven wards at two Swedish hospitals as part of a larger quasi-experimental intervention study. The majority (79%) had influence over their work schedules. Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
0
0
Order By: Relevance
“…Te results also demonstrated that working hours are highly intertwined with contextual factors, such as the work procedures on the wards (organisational factor). For example, consistent with previous fndings [57], quick returns were believed to facilitate work on the morning shift, leading some individuals to prefer those shift combinations. Tus, the way in which work procedures are organised can infuence preferences for certain shift combinations, while the removal of certain shift combinations may hinder work procedures and diminish employees' satisfaction.…”
Section: Discussionsupporting
confidence: 65%
“…Te results also demonstrated that working hours are highly intertwined with contextual factors, such as the work procedures on the wards (organisational factor). For example, consistent with previous fndings [57], quick returns were believed to facilitate work on the morning shift, leading some individuals to prefer those shift combinations. Tus, the way in which work procedures are organised can infuence preferences for certain shift combinations, while the removal of certain shift combinations may hinder work procedures and diminish employees' satisfaction.…”
Section: Discussionsupporting
confidence: 65%